Effect of Adding Different Concentrations of the Mint oil Mentha spicata L. to the Ration on Some Blood Traits of Broiler Chicks Ross 308 - Nihad Abdul-Lateef Ali (Journal of Global Pharma Technology, 2018)
This study was conducted at poultry farm of Animal Resources Dept., College of Agriculture, and University of AL-Qasim Green to investigate the effect of adding different concentrations of the Mint oil Menthaspicata L. to the ration on some blood traits of broiler chicks Ross 308. Use the 144 broiler chicks Ross 308 day-old were randomly assigned to four treatments by 3 replicates per treatment (12 chicks per replicate). The treatments were as follows: The first treatment (control) without adding mint oil to the ration. Adding mint oil at a concentration of 600 mg / kg basal feed (second treatment). While third treatment had mint oil at a concentration of 800 mg / kg feed. Adding mint oil at a concentration of 1000 mg / kg feed (fourth treatment). The study included the following characteristics: red blood cell counts, white blood cell counts, hematocrit, hemoglobin concentration and differential leucocyte count. The results indicated that the addition of mint oil at a concentration of 600 ، 800 and 1000 mg / kg feed to broiler ration led to a significant improvement in white blood cell counts of broiler chick’s ، and addition of 1000 mg Mint oil / kg of significantly improved the lymphocytes cell compared to the first treatment (control) and the second treatment. Keywords: Mint oil, Broiler chicks, Blood parameters.